P-cadherin expression in Merkel cell carcinomas is associated with prolonged recurrence-free survival - Vlahova, Lyubomira Dimcheva; Dörflinger, Yvette; Weiß, Christel; Helmbold, Peter; Goerdt, Sergij; Ludwig-Peitsch, Wiebke (British journal of dermatology, 2012)
Background Merkel cell carcinoma (MCC) is a highly aggressive skin cancer, associated with advanced age, immunosuppression and Merkel cell polyomavirus (MCV) infections. As development and progression of cancer can be promoted by changes in cell adhesion proteins, we have previously analysed homo- and heterotypic cell-cell contacts of normal Merkel cells and MCCs and obtained indications for cadherin switching. Objectives To examine the prevalence and prognostic relevance of E-, N- and P-cadherin in MCCs. Methods Paraffin-embedded MCC samples (n = 148) from 106 different patients were analysed by double-label immunostaining and immunofluorescence microscopy. MCV status was determined by real-time polymerase chain reaction. The cadherin repertoire and MCV status were correlated to clinical data, including tumour stage and recurrence-free survival. Results Ninety-one per cent of all MCC were positive for N-cadherin whereas only 61·6% and 70·3% expressed E- and P-cadherin, respectively. P-cadherin was significantly more frequent in primary tumours than in lymph node metastases (81·9% vs. 40·9%, P = 0·0002). Patients with P-cadherin-positive primary tumours were in earlier tumour stages at initial diagnosis (P = 0·0046). Both in log-rank tests (P = 0·0474) and in multiple Cox regression analysis including age, sex, immunosuppression, stage at initial diagnosis and MCV status (hazard ratio 0·193, P = 0·0373), patients with P-cadherin-positive primary MCCs had significantly prolonged recurrence-free survival (mean 25·2 vs. 10·6 months; median 9·0 vs. 4·0 months). MCV DNA was detected in 78·2% of all MCC, more frequently in P-cadherin-positive MCC (P = 0·0008). Conclusion P-cadherin expression in MCCs predicts prolonged recurrence-free survival and may therefore indicate favourable prognosis.
Gesehen am 10.10.2018